2019
DOI: 10.1002/pola.29433
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of comb‐like dispersants and a study on the effect of dispersant architecture and carbon black dispersion

Abstract: Comb dispersants suitable for stabilization of carbonaceous deposits found in automotive lubricating oils were derived from the copolymerization of vinyl‐ether terminated polyisobutylene (VE‐PIB) macromonomers with maleic anhydride (MAH). The rate and degree of copolymerization of VE‐PIB with MAH was greatly influenced by the molecular weight of the VE‐PIB. Longer PIB tails imposed greater hindrance of the chain end resulting in slower propagation and lower degrees of copolymerization for PIB‐alt‐MAH copolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…26 In addition, Storey et al demonstrated three types of polyisobutylene succinimide analog dispersants (linear, grafted, and comb type) for carbon black dispersion. 27 Compared with linear dispersants in the organic system, the comb- and grafted-type dispersants exhibited greater affinities for adsorption but decreased packing efficiencies. Despite the successful improvement of the dispersion performance via controlling polymer topologies, most of these investigations have been limited to linear polymer systems; 28–30 thus, we aim to seek further tuning of the dispersion performance via precise control of polymeric topology.…”
Section: Introductionmentioning
confidence: 98%
“…26 In addition, Storey et al demonstrated three types of polyisobutylene succinimide analog dispersants (linear, grafted, and comb type) for carbon black dispersion. 27 Compared with linear dispersants in the organic system, the comb- and grafted-type dispersants exhibited greater affinities for adsorption but decreased packing efficiencies. Despite the successful improvement of the dispersion performance via controlling polymer topologies, most of these investigations have been limited to linear polymer systems; 28–30 thus, we aim to seek further tuning of the dispersion performance via precise control of polymeric topology.…”
Section: Introductionmentioning
confidence: 98%
“…[11][12][13][14][15] According to the adsorption and dispersion mechanism of dispersants, the structure and composition of polycarboxylate comb-like dispersants such as the molecular weight, side chain length and density will have important effects on the dispersion efficiency. 10,[16][17][18] Gharanjig et al 10,18 prepared comb-like carboxylate dispersants with different molecular weights and side chain densities by copolymerization method. Their results indicate that the polycarboxylates with a larger molecular weight and a higher side chain density are more favorable for the dispersion of C.I.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the application of polycarboxylate comb‐like dispersants for the dispersion of pigments and dyes has attracted a lot of attention in the field of science and technology 11–15 . According to the adsorption and dispersion mechanism of dispersants, the structure and composition of polycarboxylate comb‐like dispersants such as the molecular weight, side chain length and density will have important effects on the dispersion efficiency 10,16–18 . Gharanjig et al 10,18 prepared comb‐like carboxylate dispersants with different molecular weights and side chain densities by copolymerization method.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the modification of St-AA-MA copolymer can be applied in many aspects. 27 Although St-AA-MA copolymers have been widely used in many fields, 28,29 they were rarely used as dispersants in disperse dyes. 30,31 In addition, the amphiphilicity of St-AA-MA copolymers needs to be improved by means of modification.…”
Section: Introductionmentioning
confidence: 99%